Sosialisasi Mitigasi Bencana Alam dan Bangunan Tahan Gempa di Desa Cibenda Kecamatan Parigi Kabupaten Pangandaran - Hasan, Fuad; Ash Siddiq, Raden Herdian Bayu; Agustian, Yanyan; Setiawan, Asep; Widyanto, Bambang Eko; Wibowo, Azis Ali (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2025)
Indonesia is highly susceptible to natural disasters, resulting in significant casualties and economic losses. The Pangandaran Regency in West Java is particularly vulnerable, especially to earthquakes and tsunamis. In 2006, a shallow earthquake with a magnitude of 7.7 triggered a tsunami along the Pangandaran coastline, primarily affecting residential, commercial, tourism, and industrial areas. The risk of disasters is a priority due to the proximity of the coast to the subduction zone and the region's history of earthquakes and tsunamis. In response to this potential threat, the Civil Engineering Study Program at Widyatama University organized a Community Service Activity focused on promoting earthquake-resistant buildings and establishing a mitigation corner to support disaster mitigation efforts in Cibenda Village, Parigi District, Pangandaran Regency. The activity involved providing educational materials on earthquake-resistant construction, setting up a mitigation corner, and distributing evacuation tools for disaster response. It is hoped that this initiative will enhance community knowledge about earthquake-resistant buildings and the use of disaster evacuation tools. The results showed a significant increase in the understanding and awareness of disaster-resilient construction and mitigation among the residents of Cibenda Village.